Pergeseran Makna Bowo Pada Pesta Pernikahan Adat Suku Nias Desa Sisobahili Kecamatan Afulu Kabupaten Nias Utara Sumatera Utara - Fiteli Waruwu; Eli Karliani; Suryadi, Suryadi (FKIP, Universitas Palangka Raya, 2024)
There has been a shift in the meaning of bowo at a traditional nias wedding party in Sisobahili Village, North Nias Regency, North Sumatra Province. This article discusses the causes of the shift in the meaning of bowo at the traditional wedding party of the nias tribe in Sisobahili Village, North Sumatra Province. This paper uses a qualitative method with the type of research is descriptive. Data collection uses the method of observation, online interview or in the form of via zoom, and documentation. The results showed that there are several factors causing the shift in the meaning of bowo at the traditional wedding party of the Nias Tribe in Sisobahili Village, North Nias Regency, North Sumatra Province, namely: the lack of efforts to pass on culture or familiarize what is usually done according to the bowo culture, changes in people's perceptions of bowo, and changes in the order in carrying out traditional wedding party events.